Analysis of pressure-induced deviation of the cricothyroid membrane among pediatric patients - Fujioka, Shoko; Hobo, Yuko; Suga, Yoshifumi; Takano, Koji; Sano, Yuri; Hosaka, Erika; Kimura, Ayano; Abukawa, Yukako (Frontiers in Anesthesiology, 2024)
Backgrounds Hypoxemia develops more quickly in children than in adults due to their high oxygen consumption relative to their body weight and small functional residual capacity. Therefore, cricothyroid puncture must be performed promptly in cannot-intubate and cannot-ventilate situations. However, the success rate of cricothyroid puncture in children is <1%. We hypothesized that the low success rate of cricothyroid puncture in children may be related to the cricothyroid membrane's hypermobility. The aim of the present study was to measure the deviation of the cricothyroid membrane from the midline when applying compressive pressure. Methods After obtaining institutional ethics committee approval, written informed consent was obtained from the patients’ parents. Children aged from 1 month to 15 years who had undergone scheduled operations under general anesthesia and with an American Society of Anesthesiologists Physical Status Classification grade of 1 or 2 were enrolled in this study. The patients were divided into the following four different age groups: 1 month–1 year, 2–4 years, 5–10 years, and 11–15 years. After the intravenous injection of fentanyl, propofol, and rocuronium, the airway was identified using a linear hockey stick ultrasound probe. The cricothyroid membrane was compressed with a force of 5 newtons (N), and cricothyroid membrane deflection was recorded. The primary outcome was the cricothyroid membrane deviation from the midline relative to the tracheal diameter. Results Twenty patients were enrolled in this study. No adverse events were noted. The mean cricothyroid membrane deviations from the midline divided by the tracheal diameter was 0.16 ± 0.09, 0.05 ± 0.04, 0.04 ± 0.04, and 0.02 ± 0.03 in children aged 1 month–1 year, 2–4 years, 5–10 years, and 11–15 years, respectively. Conclusion The cricothyroid membrane deviation due to the application of a compressive force to the overlying skin tended to be larger in younger patients.